ILLOCUTIONARY ACTS IN J.K. ROWLING’S “HARRY POTTER: THE CURSED CHILD” - Mustakim, Nur Fa'adillah; Weda, Sukardi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
This article journal aims to accomplish two objectives. The first objective is to discover the types of illocutionary acts that are found in playscript